2023
DOI: 10.1038/s41539-023-00183-w
|View full text |Cite
|
Sign up to set email alerts
|

“You did incredibly well!”: teachers’ inflated praise can make children from low-SES backgrounds seem less smart (but more hardworking)

Emiel Schoneveld,
Eddie Brummelman

Abstract: Can teachers’ inflated praise make children from low socioeconomic status (SES) backgrounds seem less smart? We conducted two preregistered experiments to address this question. We used hypothetical scenarios to ensure experimental control. An experiment with primary school teachers (N = 106, ages 21–63) showed that when a child from a low-SES (vs. high-SES) background succeeded in school, teachers attributed this success more to hard work and delivered more inflated praise (e.g., “You did incredibly well!”) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Yet, even in classrooms, children might be treated differently based on their SES. Three studies in our collection—Renoux et al 12 , Schoneveld and Brummelman 13 , and Sierksma 14 —address this possibility. They demonstrate that children from low-SES backgrounds may face unequal treatment in the classroom, often at the hands of well-intentioned teachers or peers, with serious repercussions.…”
Section: Experiences That Contribute To Achievement Inequalitymentioning
confidence: 97%
See 2 more Smart Citations
“…Yet, even in classrooms, children might be treated differently based on their SES. Three studies in our collection—Renoux et al 12 , Schoneveld and Brummelman 13 , and Sierksma 14 —address this possibility. They demonstrate that children from low-SES backgrounds may face unequal treatment in the classroom, often at the hands of well-intentioned teachers or peers, with serious repercussions.…”
Section: Experiences That Contribute To Achievement Inequalitymentioning
confidence: 97%
“…Second, teachers may send seemingly well-intentioned but discouraging messages to children from low-SES backgrounds. Working at the intersection of developmental psychology and educational science, Schoneveld and Brummelman 13 show that teachers may sometimes behave in ways that are superficially positive but undermine the perceived competence of children from low-SES backgrounds. A preregistered experiment showed that when a child from a low-SES (vs. high-SES) background succeeded in school, teachers delivered more inflated praise, such as “You did incredibly well!” Teachers probably gave more inflated praise because they inferred that the child from a low-SES background had to work harder to achieve their success.…”
Section: Experiences That Contribute To Achievement Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, teachers' unfair evaluation sometimes prompt them to behave toward students from working-class backgrounds in ways that are superficially positive but ultimately still undermining. For example, teachers might offer exaggerated praise to students from working-class backgrounds when they perform well (Schoneveld & Brummelman, 2023). While teachers' exaggerated praise may be well-intentioned, it is premised on an unfair view of working-class students as less capable than other students, which makes their good performance more surprising and thus worthy of extra praise.…”
Section: Teachers' Evaluation Of and Behavior Toward Students From Wo...mentioning
confidence: 99%
“…While teachers' exaggerated praise may be well-intentioned, it is premised on an unfair view of working-class students as less capable than other students, which makes their good performance more surprising and thus worthy of extra praise. Such overly positive teacher behaviors disadvantage students from working-class backgrounds because they and their peers can "read between the lines" and decode the subtle meaning in these behaviors: When teachers give praise that is disproportionate to the magnitude of a student's success, they must think that the student is not very capable (Schoneveld & Brummelman, 2023).…”
Section: Teachers' Evaluation Of and Behavior Toward Students From Wo...mentioning
confidence: 99%